O12 Democratising the research process: reflections on the co-production of focus groups. (20th March 2019) - Ledger, Jean; Mehta, Raj; Jasim, Sarah; Aspinal, Fiona; Barratt, Helen
Abstract : Background: Conventionally, focus groups are facilitated by academic researchers who mediate discussions with public participants. The researchers consider in advance group composition, topic guides and within-group dynamics. As part of a mixed methods evaluation of a health care improvement programme, we co-produced a series of focus groups with a patient representative. Aim: To critically reflect on the process of developing and undertaking focus groups in partnership with patient representatives, and make recommendations for others considering using a similar approach in health research. Methods: Focus group materials were co-designed with a patient representative and piloted with a patient and public advisory panel. We conducted three focus groups with individuals who had undergone surgery in the last two years (surgical groups) and individuals who had not (non-surgical group). Each group was co-facilitated with the patient representative who later contributed to discussions to interpret the findings. Results: Co-production during planning stages provided a unique patient perspective about how to communicate information to the public and emphasise the patient perspective. We re-framed the topic guide to acknowledge that the patient journey is experienced along a continuum, not bounded by time or contact points with care providers. Co-facilitation of the groups enabled transparency, legitimacy and balance of contribution across academic and lay representatives. Rather than following convention and leading a focus group, researchers' roles shifted and they became co-facilitators. Focus groups benefitted from instances where the patient representative usefully sought to extend discussions and pursue emergent topics, where academic members might have tacitly sought to stick to the topic guide and keep discussions within the remit of the study objectives. Conclusion: We suggest that this process of co-production, when instituted as part of a critically reflective team approach, democratised the research process and supported stronger engagement within the groups themselves.